Reproductive Biology of Rabbit Fish, Siganus canaliculatus (Park, 1797) along the Ratnagiri Coast of Maharashtra - S.V.Metar; V.R.Sadawarte; V.H.Nirmale; N.D. Chogale; A.N.Sawant; S.B.Satam (Journal of Indian Fisheries Association, 2023)
The fishes belonging to the family Siganidae popularly known as rabbit fishes are distributed throughout Indo-Pacific region, Rabbit fishes are considered as candidate species for mariculture due to its fast growth. Rabbit fish, Siganus canaliculatus is a marine fish inhabits coastal areas and brackish water bodies. Knowledge on reproductive biology is essential to attempt culture possibilities of this species. In the present study, an attempt is made to study the reproductive biology of this species along the Ratnagiri coast. Fishes were collected from Mirkarwada landing centre of Ratnagiri during the car 2014-16. Mean sex ratio showed equal proportion of males and females over the years. The size at maturity for males and females was estimated to be 215 mm and 245mm respectively. Gonadosomatic index (GSI) was noted to be high during the month of November for both sexes. Based on GSI values and ova diameter study the major spawning act was observed to take place between November to January. The fecundity ranged from 127335 to 875220 eggs with an average 501277 eggs